DRIVE TOURISTS: WHO ARE THEY, WHAT DO THEY DO AND HOW DO WE ATTRACT THEM? - HODA MC CLYMONT (ASEAN Journal on Hospitality and Tourism, 2007)
The research reported upon in this paper was designed to increase understanding of the demographics, and trip behaviours (such as pre-trip planning, preferred attractions and activities characteristics) of drive tourists in rural areas in order to develop promotional strategies. A mail survey targeting 960 drive tourists travelling through Goondiwindi was carried out in 2003 returning 156 usable questionnaires. Findings of this research indicated that this despite the differences in demographics, similar behaviours were exhibited by this market for most but not all trip planning behaviours including information sou activity clusters that they were most interested in participating in. A significant outcome of the research is an enhanced understanding of these characteristics which will enable rural communities to develop more effective promotional strategies in the drive tourism sector.